1955
DOI: 10.1111/j.1365-2621.1955.tb16820.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Potato Texture.

Abstract: The writers ' previous studies on starch content ( 2 ) and pectic materials (3) did not, in themselves, fully clarify the relationship of the texture of cooked potatoes with various chemical attributes. Consequently, the question arises whether differences in texture are related to differences either in the ease with which the cells can be separated or in the actual extent of cell separation in the tissues of the cooked potatoes.Various approaches to the problem of estimating the extent of intercellular spaces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

1957
1957
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(7 citation statements)
references
References 11 publications
2
5
0
Order By: Relevance
“…In the case of cell wall constituents, cell separation is thought to be due to middle cell wall and lamellar constituents. Sterling and Bettelheim () reported that a weak middle lamella allowed separation of cells. Dissolution of calcium‐pectic gel in the middle lamella has a significant role in its weakness and so results in the separation of cells (Jarvis and Duncan ).…”
Section: Mealiness Phenomenonmentioning
confidence: 99%
“…In the case of cell wall constituents, cell separation is thought to be due to middle cell wall and lamellar constituents. Sterling and Bettelheim () reported that a weak middle lamella allowed separation of cells. Dissolution of calcium‐pectic gel in the middle lamella has a significant role in its weakness and so results in the separation of cells (Jarvis and Duncan ).…”
Section: Mealiness Phenomenonmentioning
confidence: 99%
“…The amount of soluble pectic substances in raw potato tuber is relatively small (Le Tourneau, 1956; Sterling and Bettelheim, 1955). We made no effort to determine its value, and much of its was undoubtedly lost.…”
Section: Table III Composition Of Hemicellulosementioning
confidence: 99%
“…k Ithough the cell wall and middle lamella of potato tuber tissue constitute only a minor portion of the total solids present in the tuber, this material has a profound effect on the textural properties of both the raw tuber as well as of the processed potato tissue. Sterling and Bettelheim (1955) succeeded in describing the principal factors determining the textural properties of cooked potatoes. Still, the detailed chemical composition of the cell wallmiddle lamella has yet to be described.…”
mentioning
confidence: 99%
“…Any realistic attempt to determine the basis of texture must, therefore, consider a number of characteristics. Factors considered contributory to the texture of fruits and vegetables include cell wall polysaccharides (Albersheim, 1965;Joslyn, 1962; Sterling, 1963); cellular adhesion (Kertesz, 1951); starch content (Sterling and Bettelheim, 1955); and soluble solids (Hartman and Gaylord, 1941). While cell turgor is presumed to affect textural quality (Crafts et al, 1949;Strohmaier, 1953), the nature and extent of its relationship to texture has not been explored extensively in fruits.…”
Section: Introductionmentioning
confidence: 99%